Description of antemortem inspection of cattle at the Dimoro slaughterhouse, Blitar City - Hasibuan, Sandi Aziz; Lokapirnasari, Widya Paramita; Triakoso, Nusdianto; Budiarto, Budiarto; Warsito, Sunaryo Hadi; Raharjo, Dadik (Jurnal Agro Veteriner, 2025)
The outbreaks of Foot and Mouth Disease (FMD) and Lumpy Skin Disease (LSD) in early 2024 significantly impacted livestock health conditions in Blitar City and led to an increase in emergency slaughter cases. The Dimoro Slaughterhouse plays a crucial role in ensuring the safety of animal-derived food through the implementation of antemortem inspections. This study aims to evaluate the health status of beef cattle and identify pathological conditions detected during antemortem inspections at the Dimoro Slaughterhouse. The research used a quantitative descriptive method with direct observation of 40 cattle during the period of June 13–19, 2025. Clinical examinations were conducted on the head, neck, thorax, abdomen, anus, and limbs. The results showed that most cattle were male (34 heads) and predominantly of the Limousin breed (19 heads). No clinical symptoms of FMD, LSD, fever, or other disorders warranting slaughter rejection were found. Mild findings such as dirt around the anus were recorded in some individuals. Overall, the antemortem inspection was carried out effectively and contributed to ensuring the safety of meat products for public consumption.